Respostas
respondido por:
1
f(x) = x² - 5x + 6
a = 1, b = - 5 e c = 6.
Δ = b² - 4ac
Δ = (-5)² - 4(1)(6)
Δ = 25 - 24
Δ = 1
x = - b ± √Δ / 2a
x = - (-5) ± √1 / 2(1)
x = 5 ± 1 / 2
x1 = 5 + 1/2
x1 = 6/2
x1 = 3
x2 = 5 - 1/2
x2 = 4/2
x2 = 2
Letra C) 2 e 3.
Espero ter ajudado!
aurora1553:
Sim
respondido por:
1
Resposta:
Alternativa C) 2 e 3
Explicação passo-a-passo:
x² - 5x + 6 = 0
a = 1; b = - 5; c = 6
∆ = b² - 4 . a .c
∆ = (-5)² - 4 . 1 . 6
∆ = 25 - 24
∆ = 1
x = - b ± √∆ / 2 . a
x = - (-5) ± √1 / 2 . 1
x = 5 ± 1 / 2
x' = 5 + 1 / 2
x' = 6/2
x' = 3
x" = 5 - 1 / 2
x" = 4/2
x" = 2
S = {2 , 3}
Alternativa C)
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás